2019
DOI: 10.1093/humrep/dez252
|View full text |Cite
|
Sign up to set email alerts
|

T-cadherin inhibits invasion and migration of endometrial stromal cells in endometriosis

Abstract: STUDY QUESTION What is the expression level of T-cadherin in endometriosis, and does T-cadherin play a role in regulating invasion and migration of endometrial stromal cells? SUMMARY ANSWER T-cadherin expression was reduced in ectopic endometriotic lesions compared to eutopic endometrium, and T-cadherin overexpression inhibited the invasion and migration of endometrial stromal cells. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 32 publications
1
16
0
Order By: Relevance
“…In the same study, 40 endometriosis tissues were examined, and it was not clearly stated how many of these tissues were DIE tissues. In the cell culture phase of the study, it was shown that T-cadherin inhibits invasion and migration of endometrial stromal cells in endometriosis [21]. In the current study, E-cadherin level was found to be low in endometriotic nodule tissue, in accordance with the literature.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In the same study, 40 endometriosis tissues were examined, and it was not clearly stated how many of these tissues were DIE tissues. In the cell culture phase of the study, it was shown that T-cadherin inhibits invasion and migration of endometrial stromal cells in endometriosis [21]. In the current study, E-cadherin level was found to be low in endometriotic nodule tissue, in accordance with the literature.…”
Section: Discussionsupporting
confidence: 90%
“…In the literature examining T-cadherin level in endometriosis tissue, T-cadherin level was found to be low in endometriosis tissue [21]. It was shown that the expression of E-cadherin was decreased in endometriotic nodule tissue [22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…T-cadherin regulates cell migration and target nding by reducing homologous and heterophilic interactions involved in adhesion [21]. Downregulation of T-cadherin has been implicated in the progression of various carcinomas [22]. The upregulation of T-cadherin reduces the malignant characteristics of human prostate cancer, melanoma, breast cancer and liver cancer cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…Endometriosis is not a cancerous disease, but endometriotic lesions have cancer-like traits, including cell invasion and migration [16]. Endometriotic epithelial cell lines, such as 12Z, have shown enhanced migratory potential compared to normal endometrial epithelial cells [17].…”
Section: Introductionmentioning
confidence: 99%